한국 학령기 ADHD 아동을 위한 인지행동중재의 효과 연구: 메타분석 - 박완주; 박신정; 황성동; Park, Wan-Ju; Park, Shin-Jeong; Hwang, Sung-Dong (Journal of Korean Academy of Nursing, 2015)
Purpose: This study was a meta-analysis designed to identify effects of Cognitive Behavioral Therapy (CBT) interventions in alleviating main symptoms of Attention Deficit Hyperactivity Disorder (ADHD) among school-aged children in Korea. Methods: Examination of several databases including Research Information Sharing Service, Korean Studies Information Service System, Data Base Periodical Information Academic and hand-searched article references, resulted in identification of 1,298 studies done between 2000 and 2013 of which 21 met the inclusion criteria. Comprehensive Meta-Analysis version 2.0 was used to analyze effect sizes, explore possible causes of heterogeneity, and check publication bias with a funnel plot and its trim-and-fill analysis. Results: Overall effect size of CBT intervention was large (g=1.08) along with each outcome of self-control (g=1.26), lack of attention (g=1.02), social skills (g=0.92), and hyperactivity (g=0.92). For heterogeneity, moderator analysis was performed, but no significant differences were found between the RCT (Randomized Controlled Trials) group and the NRCT (Non RCT) group. Also, meta-regression was performed using sample size, number of sessions, and length of session as predictors, but no statistically significant moderators were found. Finally, a funnel plot along with trim-and-fill analysis was produced to check for publication bias, but no significant bias was detected. Conclusion: Based on these findings, there is clear evidence that CBT intervention has significant positive effects on the main symptoms of school-aged children suffering ADHD. Further research is needed to target diverse age groups with ADHD along with more RCT studies to improve the effectiveness of the CBT intervention.